Alasan Nasabah Non Muslim Memilih Pembiayaan Murabahah di Bank Syariah (Studi Kasus Nasabah di BNI Syariah KC. Rungkut Surabaya) - Azmi, Amaliah Al; Fauzy, R. Moh. Qudsi (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
This research aims to find the reason of non muslim customers chose murabahah as their funding at BNI Syariah and to find the benefit after they got those funding. This research was conducted at BNI Syariah Branch Office Rungkut Surabaya, involving of 6 non muslim customers as prime respondents and 3 employees of BNI Syariah as second respondent. Data were collected by interviewing the respondents and then the answers compared with the data from marketing or Account Officer as source triangulation. Purposive sampling technique was chosen because there were some criteria to be respondent in this research, that are: the customer should be non muslim and using murabahah. The result of this study showed that there were 3 reason of non muslim customers to choose murabahah as their choice, the first reason was the simplicity of scheme, second reason was the promotion, and the third reason was profit.